Electron‐Transporting Bis(heterotetracenes) with Tunable Helical Packing. (28th June 2018) - Zeng, Cheng; Xiao, Chengyi; Feng, Xinliang; Zhang, Lei; Jiang, Wei; Wang, Zhaohui
Abstract: A novel kind of electron‐deficient bis(heterotetracenes) namely perylenotetrathiophenediimides (PTTIs) involving double S‐hetero[5]helicene diimides, is developed by a fourfold thienannulation route via ortho ‐functionalization of perylene diimides (PDIs). PTTIs exhibit significantly red‐shifted absorption capacity with lowest‐energy transition maxima beyond 700 nm and narrowed HOMO–LUMO energy gaps. Through delicately tuning the side‐chain substitution, the distorted propeller‐like framework could self‐assemble into unprecedented 1D helical π‐stacking structures with short π–π contacts and rich nonbonding interactions from alternating arrangements ofP /M enantiomeric couples or tetrads. Excellent electron transporting efficiency in racemate PTTI crystals with 0.40 cm 2 V −1 s −1 for5 a and 0.90 cm 2 V −1 s −1 for5 b, was witnessed in single‐crystalline transistors, signifying the prospects of the chiral π‐helix in optoelectronic applications.